Evidence for three separate genes encoding the proteins of the mycobacterial antigen 85 complex. - Wiker, H G (1990)
The secreted Mycobacterium bovis BCG antigen 85 complex, which is known to bind to human fibronectin, consists of three closely related cross-reacting antigens. Amino-terminal sequence analysis of the purified proteins showed distinct differences. Data are presented to show that the three components are produced by individual cells, which indicates that three separate genes are involved.